Neoadjuvant target therapy of differentiated thyroid cancer (clinical observation) - P. A. Isaev; S. V. Vasilkov; I. S. Pimonova; F. E. Sevrukov; V. V. Polkin; D. Yu. Syomin; A. A. Ilyin; V. S. Medvedev; N. K. Silantyeva; T. A. Agababyan (Опухоли головы и шеи)
In the article a case of non-resectable differentiated thyroid cancer (DTC) is described. A recurrent thyroid tumor deforms the oropharyngeal lumen and laryngeal vestibule and bears down on the left esophageal wall and trachea. The authors present literature data on Nexavar target therapy and focus on the fact that no cases of combination treatment with target therapy and surgery of non-resectable progressive DTC were described until now. In view of this, this clinical report is unique and dictates a need to determine new Nexavar (Sorafenib) indications for use in a neoadjuvant regimen.